Social Attention in a Virtual Public Speaking Task in Higher Functioning Children With Autism. Issue 5 (20th May 2013) - Jarrold, William; Mundy, Peter; Gwaltney, Mary; Bailenson, Jeremy; Hatt, Naomi; McIntyre, Nancy; Kim, Kwanguk; Solomon, Marjorie; Novotny, Stephanie; Swain, Lindsay
<x xml:space="preserve">Abstract</x> Impairments in social attention play a major role in autism, but little is known about their role in development after preschool. In this study, a public speaking task was used to study social attention, its moderators, and its association with classroom learning in elementary and secondary students with higher functioning autism spectrum disorder (HFASD). Thirty‐seven students with HFASD and 54 age‐ and intelligence quotient (IQ)‐matched peers without symptoms of ASD were assessed in a virtual classroom public speaking paradigm. This paradigm assessed the ability to attend to nine avatar peers seated at a table, while simultaneously answering self‐referenced questions. Students with HFASD looked less frequently to avatar peers in the classroom while talking. However, social attention was moderated in the HFASD sample such that students with lower IQ, and/or more symptoms of social anxiety, and/or more attention deficit/hyperactivity disorder inattentive symptoms, displayed more atypical social attention. Group differences were more pronounced when the classroom contained social avatars versus nonsocial targets. Moreover, measures of social attention rather than nonsocial attention were significantly associated with parent report and objective measures of learning in the classroom. The data in this study support the hypothesis of the Social Attention Model of ASD that social attention disturbance remains part of the school‐aged phenotype of autism that is related to syndrome‐specific problems in social learning. More research of this kind would likely contribute to advances in the understanding of the development of the spectrum of autism and educational intervention approaches for affected school‐aged children. Autism Res 2013, ●●: ●●–●●. © 2013 International Society for Autism Research, Wiley Periodicals, Inc.